Reconceptualising Summative Assessment for Sustainable Design and Technology Teacher Development in Zimbabwe - Florence Sebele; Faith Nomathemba Tlou; Elphina Mhlanga (Scientia Publica Media, 2026)
Student wellness and professional competence in Design and Technology (D&T) within Continuous Professional Teacher Development Programs (CPTDPs) are influenced by the design and implementation of summative assessment (SA). While conventional assessments often emphasise rote learning, sustainable and technology-enhanced approaches can foster higher-order skills, creativity, and real-world problem-solving aligned with national development priorities. This study investigated the nature of SA practices in D&T CPTDPs in Zimbabwe, explored students’ and facilitators’ perceptions of their effectiveness, and identified strategies to enhance assessment in line with sustainability pedagogy, technological integration, and Education 5.0 and Vision 2030 objectives. A qualitative, narrative inquiry approach was employed, involving interviews with facilitators, focus group discussions with students, and document analysis of assessment policies, moderation reports, and curriculum materials. Data were analysed thematically and interpreted through the lens of the Technological Pedagogical Content Knowledge (TPACK) framework and sustainability pedagogy, providing insights into both educator capacity and the alignment of assessment with sustainable, higher-order competencies. Findings indicate a persistent dominance of traditional, examination-focused SA, supplemented inconsistently by project-based and applied tasks. Participants reported that conventional assessments constrained creativity, problem-solving, and sustainability-oriented learning, although instances of practical, community-based tasks demonstrated partial alignment with intended outcomes. Barriers included limited technological competence, insufficient institutional support, and constrained assessment literacy. Strategies for improvement highlighted the need for multimodal, technology-enhanced, and authentic assessments, coupled with professional development, policy alignment, and infrastructure support. In conclusion, while current SA practices provide a baseline for evaluating learning, reforms are required to foster higher-order, sustainable competencies in D&T. Integrating technology, sustainability principles, and supportive institutional frameworks can enhance student learning, innovation, and alignment with national priorities, providing actionable guidance for educators, institutions, and policymakers.